Approximation properties of modified Jain-Gamma operators - Erdogan, S.; Olgun, A. (Carpathian Mathematical Publications, 2021)
In the present paper, we study some approximation properties of a modified Jain-Gamma operator. Using Korovkin type theorem, we first give approximation properties of such operator. Secondly, we compute the rate of convergence of this operator by means of the modulus of continuity and we present approximation properties of weighted spaces. Finally, we obtain the Voronovskaya type theorem of this operator.